2022
DOI: 10.1186/s12893-022-01529-8
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative neutrophil-to-lymphocyte ratio may contribute to the prediction of postoperative infectious complications in patients with acute appendicitis: a retrospective study

Abstract: Background Several studies have assessed various clinical variables to identify risk factors for postoperative complications in patients with acute appendicitis. However, few studies have focused on the relationships between systemic inflammatory variables and postoperative complications in patients with acute appendicitis. We investigated the relationships between postoperative complications and systemic inflammatory variables, and assessed the clinical utility of these variables as predictors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
0
1
0
Order By: Relevance
“…Recently, several studies have demonstrated the potential utility of the NLR, PLR, MLR, and SII in the diagnosis of PJI following TJA [66][67][68][69][70][71][72] . While these inflammatory ratios have been used as predictors of postoperative complications, including infection and mortality, in other surgical specialties, their preoperative utility has yet to be demonstrated in the arthroplasty literature [53][54][55][56][57][58][59][60][61][62][63][64][65] . Our study showed that, among morbidly obese patients who underwent TJA, the risk of PJI increased 2.38-fold if their preoperative NLR was >3.31, 4.86-fold with a PLR of >182.30, and 2.44-fold with an SII above 776.20.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, several studies have demonstrated the potential utility of the NLR, PLR, MLR, and SII in the diagnosis of PJI following TJA [66][67][68][69][70][71][72] . While these inflammatory ratios have been used as predictors of postoperative complications, including infection and mortality, in other surgical specialties, their preoperative utility has yet to be demonstrated in the arthroplasty literature [53][54][55][56][57][58][59][60][61][62][63][64][65] . Our study showed that, among morbidly obese patients who underwent TJA, the risk of PJI increased 2.38-fold if their preoperative NLR was >3.31, 4.86-fold with a PLR of >182.30, and 2.44-fold with an SII above 776.20.…”
Section: Discussionmentioning
confidence: 99%
“…These values are commonly utilized as screening metrics for patients undergoing TJA and have previously been identified as predictors of postoperative complications following TJA [21][22][23][24]26,27,[43][44][45][46][47][48][49][50][51][52] . The NLR, MLR, PLR, and SII were included to investigate their preoperative utility to predict PJI due to their proven function as diagnostic markers of PJI and as preoperative predictors of complications in other surgical specialties [53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72] . Laboratory values were categorized as abnormal using established clinical thresholds.…”
Section: Identification Of Predictive Preoperative Laboratory Valuesmentioning
confidence: 99%
“…The capacity of NLR to distinguish between simple and complicated appendicitis in pediatric patients, as measured by the AUC, ranges from 0.66 to 0.84, with cut-off points between 4.8 and 10.4 and a sensitivity of 67–85% [ 18 ]. Mori et al demonstrated that an increased NLR is a good predictor of postoperative infections in children with acute appendicitis [ 43 ].…”
Section: Discussionmentioning
confidence: 99%